Prognostic impact of cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) in gastric cancer patients: A meta-analysis of randomized controlled trials. Issue 11 (November 2021) - Granieri, Stefano; Bonomi, Alessandro; Frassini, Simone; Chierici, Andrea Piero; Bruno, Federica; Paleino, Sissi; Kusamura, Shigeki; Germini, Alessandro; Facciorusso, Antonio; Deraco, Marcello; Cotsoglou, Christian
Abstract: Background: gastric cancer patients frequently develop peritoneal metastases (PM) with a poor long-term prognosis. A solid body of evidence underlines the beneficial role of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) on survival, but to date, there is a lack of consensus regarding the optimal strategy in the treatment of locally advanced primary tumors with or without peritoneal metastasis. The present meta-analysis aims to assess the impact of CRS + HIPEC on survival analyzing the results of randomized studies only. Methods: A systematic review of articles was conducted according to PRISMA guidelines. Twelve studies were included in qualitative and quantitative analysis. Results: A survival benefit for patients treated with CRS + HIPEC at all time points was highlighted. However, difference in survival was significant at all time points for patients treated for prophylaxis of PM, but no difference was found when considering resection with a curative intent. The 1, 2, 3 and 5-year survival rates (SR) for patients undergoing CRS + HIPEC were 86.9%, 70.5%, 63.7% and 55.7% respectively. CRS + HIPEC for the treatment rather than prophylaxis of PM was the only predictor of a reduced 3y SR. Conclusions: CRS + HIPEC may lead to improved prognosis for patients suffering from locally advanced gastric cancer in both prophylactic and curative settings. However, due to far from negligible postoperative morbidity and mortality rates, a strict patient selection is crucial to achieve the best results. The presence of extraperitoneal disease strongly limits the indication of this kind of surgery.